2021
DOI: 10.1101/2021.11.06.467095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crosstalk between β-catenin and WT1 signalling activity in acute myeloid leukemia

Abstract: Article summaryβ-Catenin is frequently dysregulated in acute myeloid leukemia (AML) and protein interactions govern its stability, localisation and activity, but these are poorly defined in AML.This study shows for the first time that β-catenin and Wilms tumour protein (WT1) interact and influence each other’s expression level and signalling activity in AML cells, which could inform future therapeutic strategies.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Proteomic studies have revealed for the first time that β-catenin also interacts with Wilms tumour protein (WT1), in an RNA-independent manner. Interestingly, these studies demonstrated that β-catenin also co-localised with WT1 in the nucleus during Wnt activation [ 37 , 38 ]. Since this was confirmed in the HL-60 cells, in addition to primary samples, and that we have shown inhibition of β-catenin in multiple AML cell lines, it would be interesting to distinguish whether NUC-7738 also inhibits WT1 and whether this heightens the anti-leukemic response.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies have revealed for the first time that β-catenin also interacts with Wilms tumour protein (WT1), in an RNA-independent manner. Interestingly, these studies demonstrated that β-catenin also co-localised with WT1 in the nucleus during Wnt activation [ 37 , 38 ]. Since this was confirmed in the HL-60 cells, in addition to primary samples, and that we have shown inhibition of β-catenin in multiple AML cell lines, it would be interesting to distinguish whether NUC-7738 also inhibits WT1 and whether this heightens the anti-leukemic response.…”
Section: Discussionmentioning
confidence: 99%